PENERAPAN PROBLEM BASED LEARNING BERBANTUAN MEDIA WORDWALL UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Moh Efendi; Andi Nurwati; Zohrawati Hiola (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to determine the application of the problem-based learning model assisted by WordWall media in increasing students' interest in learning science in grade IV of SDN 08 Gadung. This type of research is classroom action research. The subjects of this study were grade IV at SDN 08 Gadung totaling 23 people. The data analysis techniques used in this study were analysis of observation results and analysis of questionnaire results. Based on the results of the study, it can be concluded that learning science using the Problem Based Learning learning model assisted by WordWall media is proven to increase the interest in learning of grade IV of SDN 08 Gadung. This is indicated by an increase in the percentage of student interest in learning from cycle I to cycle II. In cycle I, the percentage of student interest in learning was still at a sufficient level, reaching 71%. At this stage, students still seemed less enthusiastic, their attention was easily distracted, and they were not very active in participating in learning activities. After optimal learning was implemented in cycle II, the percentage of student interest in learning experienced a significant increase to 82%. This means that there was an increase in the percentage of 11% compared to the previous cycle.